Rediscovery of Cerroneuroterus apenninus (Trotter, 1923) (Hymenoptera: Cynipidae: Cynipini) a valid species from Italy with description and neotype designation - Cerasa, Giuliano; Sottile, Salvatore; Massa, Bruno; Verde, Gabriella Lo (Zootaxa, 2021)
Neuroterus apenninus Trotter, 1923 associated with a Cerris section oak, Quercus cerris L., was rediscovered in Italy in 2017. Alessandro Trotter (1903) described a leaf gall collected on Q. cerris from the Italian Apennines; he did not obtain the gall inductor and ascribed the galls to the genus Neuroterus, based on morphological similarity with other Neuroterus galls. We have found the same gall and obtained the gall inducer. Detailed study of morphological characters of adults revealed that the species belongs to the genus Cerroneuroterus Melika & Pujade-Villar, 2010. The asexual generation of Cerroneuroterus apenninus comb. n. is described for the first time, a neotype is designated, and a diagnosis, host associations and biological notes are given; an identification key to the Western Palaearctic Cerroneuroterus species is provided.